Contradictory working length effects in locked plating of the distal and middle femoral fractures―a biomechanical study. (December 2020) - Chao, Ching-Kong; Chen, You-Lin; Wu, Jian-Ming; Lin, Chen-Huei; Chuang, Ting-Yu; Lin, Jinn
Abstract: Background: Working length have been reported to affect the plate stress and fixation stiffness. However, the results of previous studies have been controversial. The present study was to determine working length effects on different locations of femoral bone gap. Methods: Five composite femurs with wide bone gaps at five levels (G1, 2, 3, 5, and 7), were fixed with locking plates. G1-3, G5 and G7 represented gaps at distal femur, distal-middle femur and middle femur respectively. Strain gauges were applied near the screw holes. The plate-bone constructs were loaded through a hemicylinder on the femoral head with total constraints at the distal femur. The micro-strains, axial stiffness and interfragmentary motions were recorded. Then the locking screws were removed one by one and the tests were re-run. The working length effects were compared and correlated. Findings: In distal femurs (G1-3), long working length was negatively correlated with the highest strains ( r = −0.97, −0.95 and − 0.95, p < 0.01) and axial stiffness ( r = −1, −0.96 and −0.99, p < 0.01). In distal-middle femurs (G5), as the working length increased, the highest strain decreased initially and then increased ( r = 0.81, p = 0.026) and the axial stiffness decreased ( r = −0.98, p < 0.01). In middle femurs (G7), the highest strain and gap motions were much higher than that in the other groups and not significantly correlated with the working length change. Interpretation: Long working length could reduce the highest plate strain in distal femurs, but had no significant effects in middle femurs. The working length effects were markedly affected by the loading and boundary conditions. Highlights: Long working length reduces plate strain in distal femur but not in middle femur. Leaving two screw holes empty around fracture site is acceptable for distal femoral fixation. Screw position change can reduce plate strain rather than screw number reduction. Working length effects were affected by the loading and boundary conditions.